Hubungan Tingkat Efektivitas dan Kejenuhan (Burnout) Pada Mahasiswa Pendidikan Vokasi Dalam Pembelajaran Daring - Novita Alfiani (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
Vocational education is higher education that prepares students for jobs with specific skills up to an applied master's program. The occurrence of a pandemic has made the learning system change from face-to-face learning to bold learning. Bold learning causes burnout which results in physical and mental exhaustion. This study aims to determine the relationship between the level of effectiveness and saturation of vocational education students participating in bold learning. This type of research is an analytic survey using a cross-sectional design. The number of samples is 79 people. The sampling technique used is total sampling. Data was collected at the D III X-Ray Engineering Study Program, Widya Husada University, Semarang. The statistical test used is the chi-square test. The results of the univariate analysis showed that 53 respondents (67.1%) stated that bold learning was ineffective. In the burnout category, which was obtained from 79 respondents, 34 respondents (43%) had low burnout, 41 respondents (51.9%) had moderate burnout, and four respondents (5.1%) had high burnout. A statistical test was obtained, with a p-value of 0.002 of 0.05. This result shows a significant relationship between courageous learning and burnout. It was found that the value of r = -.341 indicates the direction of the negative correlation or a non-unidirectional relationship, which indicates the more influential the bold learning, the lower the burnout with sufficient interpretation between courageous education and students. It is hoped that the results of this study can be a reference for the government and educational institutions to pay more attention to the quality and facilities of both facilities and infrastructure to improve an effective bold learning system.